“Bargaining with Patriarchy” and Entrepreneurship: Narratives of Malay Muslim Women Entrepreneurs in Malaysia - Nor Hafizah Selamat; Noraida Endut (Kajian Malaysia, 2020)
Achieving gender equality and women’s empowerment is integral to Sustainable Development Goals (SDGs) and it has been emphasised that women have a key role in achieving SDGs. Towards the 2030 Agenda for Sustainable Development, what is the reality of gender equality in women’s entrepreneurship? The Malaysian government has provided various platforms to increase women’s participation in entrepreneurship. However, the relatively meagre research exploring the lived experiences of women entrepreneurs in Malaysia where patriarchy is strongly embedded in the society has created a big gap in the literature. By using the gender lens and Kandiyoti’s concept of bargaining patriarchy, this article explores how women entrepreneurs are constantly negotiating and at the same time conforming to patriarchal norms to earn their own “space and freedom” in running and managing their business activities. Ten women entrepreneurs of Amanah Ikhtiar Malaysia (AIM) were interviewed. It is revealed that women entrepreneurs have to constantly juggle their time between performing their domestic duties and their entrepreneurship through constant negotiation with the patriarchal norms. This study offers new insights on negotiating patriarchy used by the women entrepreneurs as a strategy to run their business activities. The gender lens used managed to unravel the fact that Malay Muslim women entrepreneurs are not just passive recipients of patriarchal norms, but consciously and constantly strategise and negotiate their way within the constraints of living in a patriarchal society.